The role of plant oils/lipids as innovative fat replacers in various food products: A review - Kok Jia-Wei; Ming Fu; Abu Bakar Asyrul-Izhar; Lilis Suryaningsih; Dicky Tri Utama; Kazem Alirezalu; Mohammad Rashedi Ismail-Fitry (Applied Food Research)
Due to growing demands for palatable and nutritious food products, liquid plant oils are structured into oleogels and emulsion gels as fat replacers to mimic the physical state of saturated fats. This work reviews the methods of structuring plant oils into fat replacers and the functionality of these fat replacers, including emulsions and liquid oils, based on their recent applications in meat, bakery, and dairy products. Oleogel is made either by direct or indirect oleogelation, whereas the structuring of a biphasic system generates emulsion gels. The type of gelator and plant oil used influenced the colour, texture, and sensory properties of food products. The plant oil type also affected the fatty acid composition and oxidative stability of food. Textural properties were also altered where hardness was the most emphasised and affected, but the changes did not always deteriorate the overall acceptability of fat-replaced samples. Plant oil fat replacers efficiently enhance the fatty acid composition of food products by increasing unsaturated fatty acid content and reducing saturated and trans fatty acid content. However, most products were prone to lipid oxidation, which produced off-flavour compounds that compromised sensory acceptance, therefore, antioxidants could help. Oleogels, emulsion gels and emulsions were equally effective as fat replacers in various food products, and this indicated the successfulness of the oil structuring approaches. Therefore, the research on potential plant oil fat replacers should be expanded. The sensory analysis of reformulated food products is also recommended to better understand the effects of fat replacers on various food products.